Family Planning Communication between Wives and Husbands: Insights from the 2017 Indonesia Demographic and Health Survey - Irawaty, Dian Kristiani; Yasin, Suziana Mat; Pratomo, Hadi (UI Scholars Hub, 2020)
Frequent inter-spousal communication is regarded as an indicator of safe family planning practice. Nevertheless, communication about family planning within couples in Indonesia is still largely unexplored. This study assessed the levels of inter-spousal communication about family planning and its associated determinants, using cross-sectional and nationally representative data from the 2017 Indonesia Demographic and Health Survey (IDHS), from a randomly selected cohort of 8,925 currently-married couples. Data on sociodemographic characteristics, inter-spousal communication behaviors, and attitudes regarding family planning were collected. The dependent variable in this study is how frequently couples discuss family planning, based on wives’ responses. The analyses were stratified based on the frequency of inter-spousal communication: never, once or twice, or more often. The results of the study were greater husband approval of family planning and communication with family planning field workers, and that those encouraged inter-spousal communication in Indonesia.